Animal models to explore the effects of glucocorticoids on skeletal growth and structure - Wood, Claire L; Soucek, Ondrej; Wong, Sze C; Zaman, Farasat; Farquharson, Colin; Savendahl, Lars; Ahmed, S Faisal (The Journal of endocrinology, 2018)
Glucocorticoids (GCs) are effective for the treatment of many chronic conditions, but their use is associated with frequent and wide-ranging adverse effects including osteoporosis and growth retardation. The mechanisms that underlie the undesirable effects of GCs on skeletal development are unclear, and there is no proven effective treatment to combat them. An in vivo model that investigates the development and progression of GC-induced changes in bone is, therefore, important and a well-characterized pre-clinical model is vital for the evaluation of new interventions. Currently, there is no established animal model to investigate GC effects on skeletal development and there are pros and cons to consider with the different protocols used to induce osteoporosis and growth retardation. This review will summarize the literature and highlight the models and techniques employed in experimental studies to date.
Keywords: Animals; murine; growth; Bone Development; osteoporosis; Animals, Genetically Modified; poruchy růstu; Osteoclasts; lidé; glukokortikoidy; Glucocorticoids; Osteoporosis; osteoklasty; osteocyty; Skeleton; modely nemocí na zvířatech; vývoj kostí; kostra; Disease Models, Animal; Growth Disorders; glucocorticoids; mouse; zvířata; skeletal development; Osteocytes; geneticky modifikovaná zvířata; osteoporóza; Humans